The Equitable Distribution of Opportunity to Learn in Mathematics Textbooks - Morgan S. Polikoff; Sarah J. Rabovsky; Daniel Silver; Rosalynn Lazar-Wolfe (SAGE Publishing, 2021)
Low-income students and students of color are faced with pervasively lower levels of opportunity to learn compared with their peers, creating unequal opportunities for educational success. Textbooks, which serve as the backbone of the curriculum in most mathematics classrooms, present a potentially powerful tool to help mitigate unequal opportunity to learn across students. Using the Surveys of Enacted Curriculum framework, we investigate the content of commonly used eighth-grade math textbooks in California and the extent to which they align with the Common Core State Standards. We also explore the relationship between the variation in content coverage and alignment and student characteristics. We find poor alignment between the textbooks in our sample and the Common Core State Standards and low overall levels of cognitive demand, but only limited evidence of systematic differences in alignment or cognitive demand coverage associated with student characteristics at the school or district level.